Copan Walk Away Specimen Processor (WASP) Automated System for Pathogen Detection in Female Reproductive Tract Specimens - Gao, Jing; Chen, Qiujing; Peng, Yiqian; Jiang, Nanyan; Shi, Youhao; Ying, Chunmei (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Automation is increasingly being applied in clinical laboratories; however, preanalytical processing for microbiology tests and screening is still largely performed using manual methods owing to the complex procedures involved. To promote automation of clinical microbiology laboratories, it is important to assess the performance of automated systems for different specimen types separately. Therefore, the aim of this study was to explore the potential clinical application of the Copan Walk Away Specimen Processor (WASP) automated preanalytical microbiology processing system in the detection of pathogens in female reproductive tract specimens and its feasibility in optimizing diagnostic procedures. Methods Female reproductive tract specimens collected from pregnant women at their first obstetric check-up were inoculated into culture media using the Copan WASP automated specimen processing system and were also cultured using a conventional manual inoculation method. After 48 h of culture, the growth of colonies was observed, and the types of bacteria, number of colonies, and efficiency in isolating single colonies were compared between the automated and manual groups. The specimens collected from the WASP system using the Copan-ESwab sample collection tubes were further analyzed for the presence of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Ureaplasmaurealyticum (UU) via fluorescence quantitative polymerase chain reaction (qPCR) and an immunochromatographic assay to investigate the feasibility of this method in optimizing detection of these common pathogens of the female reproductive tract. Results Compared with the manual culture method, the Copan WASP microbiology automation system detected fewer bacterial types (P<0.001) and bacterial colonies (P<0.001) but had a higher detection rate of single colonies (P<0.001). There was no significant difference in the detection rates of common pathogens encountered in clinical obstetrics and gynecology, including group B Streptococcus (GBS) (P=0.575) and Candida (P=0.917), between the two methods. Specimens collected in the Copan-ESwab tubes could be used for screening of GBS and CT via fluorescence-based qPCR but not with immunochromatography. However, UU and NG were not detected in any sample with either method; thus, further validation is required to determine the feasibility of the Copan system for screening these pathogens. Conclusion The Copan WASP microbiology automation system could facilitate the optimization of diagnostic procedures for detecting common pathogens of the female reproductive system, thereby reducing associated costs.